69.1k views
4 votes
If mZFBC = (10x – 9), mZCBE = (4x + 15),
find mZFBE.

If mZFBC = (10x – 9), mZCBE = (4x + 15), find mZFBE.-example-1
User Junito
by
5.0k points

2 Answers

4 votes

Answer:

BEFmZ Is the answer i think

Explanation:

User Redux
by
5.9k points
5 votes

Answer:

mFBE = 14x + 6

Explanation:

As you can see FBE is sum of FBC + CBE

Given mFBE = mFBC + mCBE

= 10x - 9 + 4x + 15

= 14x + 6

So mZFBE = 14x + 6

User Pinakin Shah
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.